Innovative Activity of SMEs Cooperating with Scientific – Research Institutions on the basis of Wielkopolskie Voivodship - Hanna MIZGAJSKA; Łukasz WŚCIUBIAK (Communications of International Proceedings, 2021)
The aim of this article is diagnosis of innovative activity and identification of factors determining innovative activity of enterprises representing SMEs sector, cooperating with scientific – research institutions. The article is based on data collected in the course of survey research conducted amongst 63 owners of small and medium-sized enterprises from South – East territory of Wielkopolskie voivodship. The research was conducted in a time range from 2016 to 2018. Collected empirical material was developed with the use of gamma and Sperman ranks. The performed research allow to draw a conclusion that innovative activity of enterprises cooperating with scientific – research institutions is higher than activity of not cooperating enterprises, and their innovative activity stimulating factors are: entrepreneur’s competences, company’s size, automation level, economic and financial condition, as well as taking advantage of EU subventions. The following limiting factors were listed: employees’ insufficient qualifications, high implementation costs, lack of innovative policy, high taxes, confusing law regulations, lack of own financial resources, difficult access to external funding and market competition. The results obtained may also constitute a collection of recommendations for business practitioners and political decision – makers, responsible for shaping innovative policy.
Keywords: Innovation; Small and Medium – Sized Enterprises; Science – Industry Collaboration